Reaction and deformation mechanism of a slipping-stretching landslide: Example of the Liangtianao ancient landslide, Guangxi Province, China - Youjun, Li; Hongri, Zhang; Liming, Huang; Sulian, Lan; Hongming, Li; Xuexiao, Wu (Frontiers in Earth Science, 2023)
Slipping-stretching landslides have long been recognized as a common type of landslide case, but such reactions have rarely been reported. There was a slipping-stretching landslide reaction at Liangtianao, Guangxi Province, China, and the geological background and deformation characteristics of the case were identified by detailed geological survey and long-term monitoring. A FEM model of the case was built using GEO5 to analyze the mechanism of reaction and deformation. The results are as follows. 1) The Liangtianao landslide is a bedding rock ancient landslide, which remained in a creeping state after the landslide occurred in geological history. 2) The new sliding surface in the Liangtianao landslide is basically consistent with the weak interlayers formed by ancient landslides, and the fault-type is a slipping-stretching type with the following deformation process: strain at leading edge by road excavation→ leading edge instability→ middle part shear and creep→ back edge tensile. 3) Micro-geomorphology, rock mass bedding, and weak interlayers are internal causes of the Liangtianao landslide reaction, while excavation unloading and rainfall are the external causes. The inclinometer indicates that the Liangtianao landslide is still highly sensitive to rainfall after the landslide reaction, which may trigger a secondary landslide reaction. 4) The numerical analysis results indicate that the maintenance of a passive state in the anti-sliding section is highly beneficial to maintaining basic stability after the landslide reaction; unloading only 1/20 of the sliding section makes the landslide stable in the long term.